Introduction to Exercise Science - Knudson, Duane V. (Human Kinetics, 2024)
This book provides readers with an overview of the major subdisciplines of exercise science, introduces readers to the basics of quantitative research in these subdisciplines, and illustrates how interdisciplinary collaboration and applied research in exercise science-related professions contributes to the performance and health of all people.